Effects of beetroot-pineapple juice on hypertensive elderly in Depok - Fachira Nabila; Mia Srimiati (Sarana Ilmu Indonesia (salnesia), 2024)
The prevalence of hypertension, based on measurement results among the population aged ? 18 in Indonesia, increased by 8.3% from 2013 to 2018. Due to this rise, there is an evident need for treatments to decrease this rate. Introducing non-pharmacological therapies, such as beetroot and pineapple juice, maybe a viable solution. This study aimed to assess the difference in blood pressure before and after the consumption of beetroot and pineapple juice among elderly hypertensive patients in the Abadijaya Public Health Center region of Depok City. The research followed an experimental design, specifically a pretest-posttest one-group format. The study involved 15 elderly individuals aged between 60-80 years with blood pressure readings of ? 140/90 mmHg. They consumed 300 ml of the juice daily for seven consecutive days. Data analysis included the Shapiro-Wilk test for normality, the paired t-test, and the Wilcoxon test for statistical significance. The findings revealed a significant reduction in blood pressure after the consumption of beetroot and pineapple juice, with a p-value for systolic pressure at 0,000 and diastolic pressure at 0,020 (p<0,05). The average decrease in systolic blood pressure was 13,03 mmHg, and for diastolic blood pressure, it was 4,8 mmHg. There was a discernible difference in blood pressure measurements before and after juice consumption among the elderly hypertensive patients.